Determination of thresholds for key quality Traits. Quality and preferences. Task Force. - Nakitto, M.; Newilah, G.N.; Adinsi, L.; Deuscher, Z.; Otegbayo, B. (2024)
Breeding programs rely on sensory analysis including consumer tests and descriptive tests to identify priority quality traits that drive consumer liking, assess intensity of sensory characteristics in the laboratory and validate instrumental measurements of sensory characteristics. However, the quantitative targets for the priority quality traits known as desirable thresholds need to be established to facilitate breeding selections. This presentation introduced the multi-disciplinary breeding teams to the basics of sensory analysis method concepts, the steps involved in determining thresholds values for priority quality traits and provided examples of how established thresholds have been applied in different breeding programs. It was followed by a panel discussion on how multi-disciplinary teams can collaborate effectively. Breeders expressed the need for more flexibility and efficiency in the food science methods to ease integration into routine breeding activities. To improve collaboration within multi-disciplinary teams, it was proposed that food scientists play a double role as equal partner researchers while also providing analytical services in breeding programs. In addition, there was a call to include non-breeding scientists at all routine breeding stages including budgeting, product design, activity planning and product advancement. The main challenge to establishing thresholds and integrating their application is logistical which could be overcome by increasing the number of members on teams and diversifying their expertise, as well as developing methods that can be used to collect data in the field. The discussions from this meetng are expected to strengthen cooperation and collaborations within multi-disciplinary research teams to facilitate transdisciplinary approach to work for more effective project outputs and outcomes.